2001
DOI: 10.1177/002215540104900803
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-EM Localization of GFP-tagged Yolk Proteins inC. ElegansUsing Microwave Fixation

Abstract: Because of the presence of a low-permeability cuticle covering the animal, fixation of C. elegans tissue for immunoelectron microscopy has proved very difficult. Here we applied a microwave fixation protocol to improve penetration of fixatives before postembedding immunogold labeling. Using this technique, we were able to successfully localize several components of yolk (YP170) trafficking in both wild-type and transgenic strains expressing a vitellogenin::green fluorescent protein fusion (YP170::GFP). Green f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
0
29
1
Order By: Relevance
“…For simplicity, we hoped to use direct visualization of GFP fluorescence to locate the expressing cells in semithin sections. Although there are many examples of immunogold localization of GFP in the literature (Shiao et al 2000;Paupard et al 2001;Ward and Moss 2001;Thomsen et al 2002), and at least one report of immunofluorescence localization in sections of LR White-embedded material (Herken et al 1988), we found no mention of whether GFP fluorescence could be visualized directly in LR White-embedded material or whether the fluorescence and the antigenicity of GFP would be retained after overnight fixation in low concentrations of glutaraldehyde. Although GFP fluorescence previously was reported to survive glutaraldehyde fixation, the length of fixation and the concentration of fixative were not given (Chalfie et al 1994).…”
contrasting
confidence: 62%
“…For simplicity, we hoped to use direct visualization of GFP fluorescence to locate the expressing cells in semithin sections. Although there are many examples of immunogold localization of GFP in the literature (Shiao et al 2000;Paupard et al 2001;Ward and Moss 2001;Thomsen et al 2002), and at least one report of immunofluorescence localization in sections of LR White-embedded material (Herken et al 1988), we found no mention of whether GFP fluorescence could be visualized directly in LR White-embedded material or whether the fluorescence and the antigenicity of GFP would be retained after overnight fixation in low concentrations of glutaraldehyde. Although GFP fluorescence previously was reported to survive glutaraldehyde fixation, the length of fixation and the concentration of fixative were not given (Chalfie et al 1994).…”
contrasting
confidence: 62%
“…Serial thin sections were collected on slot grids and post-stained with uranyl acetate and lead citrate, and examined with a Philips CM10 electron microscope. To fix young L1s from RNAi experiments, animals were exposed to microwave irradiation during the primary fixation in buffered aldehydes, using a model 3450 oven (Ted Pella) at half power (Paupard et al, 2001). Subsequent fixation steps follow our normal protocols (Hall, 1995).…”
Section: Electron Microscopymentioning
confidence: 99%
“…Some recent papers have indicated preferential immunolabeling density by MWI (Rangell & Keller 2000, Paupard et al 2001. These results were obtained using acrylic resin (such as LR Gold, LR White) or frozen sections.…”
Section: Effect Of Mwi On Fixation and Immunolabeling Of Plastic-embementioning
confidence: 96%
“…The MWI has been widely utilized to advance biological processing: tissue fixation, histochemistry, antigen retrieval, and in situ hybridization (Shi et al 1991, Login et al 1995, Van Ginneken et al 1998, Rangell & Keller 2000, Mitchell et al 2001, Paupard et al 2001. The great increase in molecular motion induced by MWI enables fixatives to soak rapidly and deeply into cells and tissues (Boon et al 1990, Rangell & Keller 2000.…”
Section: Effect Of Mwi On Fixation and Immunolabeling Of Plastic-embementioning
confidence: 99%